Perception of pregnant women towards caesarean section in Nigeria: a case study of a missionary hospital in Edo state, Nigeria - Amiegheme, Felicia E.; Adeyemo, Florence Oluyemisi; Onasoga, Olayinka A (International Journal Of Community Medicine And Public Health, 2017)
Background: The perception of pregnant women towards caesarean section (CS) even in the face of danger has been a major concern. The major objective of the study was to investigate the perception of pregnant women attending a missionary hospital in Edo state, Nigeria. A simple random sampling technique was used to select one hundred pregnant women from the antenatal clinic the hospital. Methods: Data were collected using a structured questionnaire and analyzed using descriptive statistics in form of frequency, percentages and tables, t-test and one way analysis of variance (ANOVA) at the significance level of 5%. Results: Findings revealed that perception of pregnant women towards caesarean sections is negative/low, 79% objected delivery via CS for fear of death while 82% objected due to family preference of vaginal delivery. 60% also objected because of the cost of undergoing CS. Findings further revealed that the group of respondents who have experienced caesarean section have a more positive perception towards caesarean section than the group who haven’t. Conclusions: This study clearly indicate that there is a negative perception of pregnant women in this setting and majority of them were clearly adverse to CS. Educational level also significantly influences the perception of pregnant women towards caesarean section. It is therefore recommended that proper education of the masses be done so as to correct the wrong notions about caesarean section.